2009
DOI: 10.1177/0883073809339878
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Common Neurologic Diseases Among Israeli Adolescents

Abstract: Neurologic disorders are the common causes of morbidity among adolescents. The estimated prevalence of common neurologic disorders relies on relatively small samples. We aimed to identify the prevalence of common neurologic disorders among Israeli adolescents. In Israel, all 17-year-old Israeli nationals are required to undergo a health-screening examination at the Israel Defense Forces recruiting office. Neurology specialists evaluate and classify suspected neurologic disorders. The findings included a high p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In adults, tic prevalence rates are considerably lower, with estimates of 0.05% to 0.1% for TS, and of 0.08% to 6.7% for any tic disorders (Zohar et al 1992; Apter et al 1993; Robertson et al 1994; Eapen et al 2001; Wenning et al 2005; Bar-Dayan et al 2010; Schlander et al 2011; Knight et al 2012). A Swedish population-based twin study ( n = 21 911) found prevalence rates of 6.7% for having any tic, and 1.4% for having TS (not taking the DSM-IV-TR criterion of presence of at least one vocal tic into account) (Pinto et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In adults, tic prevalence rates are considerably lower, with estimates of 0.05% to 0.1% for TS, and of 0.08% to 6.7% for any tic disorders (Zohar et al 1992; Apter et al 1993; Robertson et al 1994; Eapen et al 2001; Wenning et al 2005; Bar-Dayan et al 2010; Schlander et al 2011; Knight et al 2012). A Swedish population-based twin study ( n = 21 911) found prevalence rates of 6.7% for having any tic, and 1.4% for having TS (not taking the DSM-IV-TR criterion of presence of at least one vocal tic into account) (Pinto et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…There are a handful of prevalence studies involving adults with TS that could provide some idea of the prevalence of adult-onset tics, but even these are quite few in comparison to the number of prevalence studies done in children 3946. In three of these studies, the population consisted of adolescents aged 16–17 years who were undergoing health screening for military service in Israel,39,40,46 and therefore not necessarily representative of the 18+ adult population. A few studies have looked at all tic disorders, thereby including secondary tics as well.…”
Section: Prevalencementioning
confidence: 99%